Factors influencing the successful adoption of online banking services in Sri Lanka - Herath, H.M.M.N; Aruppala, W.D.N. (University of Jaffna, 2024)
This study examines the factors that affect the successful adoption of online banking services in Sri Lanka. Despite the many advantages offered by online banking, its acceptance in the country remains low. To address this issue, this research applies the Technology Acceptance Model (TAM) introduced by Davis in 1989, focusing on the key attributes influencing online banking adoption. The study investigates the determinants influencing the effective deployment of online banking services in Sri Lanka, gathering data through a questionnaire distributed among internet banking users. Demographic and correlation analyses were conducted and the impact of independent variables on online banking adoption was assessed through reliability tests and path analysis with Smart PLS software. Findings reveal that factors such as perceived benefit, ease of use, and customer attitudes significantly influence the intention to use online banking services in the country. Moreover, the study highlights the advantages of online banking for both consumers and banks, including convenience, time savings, and cost efficiency. The research suggests that banks should communicate these benefits to customers to increase adoption rates and enhance service quality. The findings offer important insights for Sri Lankan banks and policymakers aiming to promote the usage of online banking and improve financial inclusion.
Keywords: Online Banking; Sri Lanka; Technology Adoption; JEL Classification: G21, O33, M15